Strategy for Increasing Legal Awareness Village Achievements Through Involvement of the Role of the Driving Team Empowering Village Family Welfare - Aman Serah, Yenny; Setiawati, Rini; Sirait, Resmaya Agnesia Mutiara (Universitas Muhammadiyah Sumatera Utara, 2024)
The aim to be achieved in this research is to realize the achievement of a Legal Awareness Village by increasing the role of Family Welfare Empowerment (PKK) at the Village Level. The PKK, which recruits members down to the lower levels of society is expected to be able to bring about prosperous family conditions, namely families that can fulfill basic human needs both materially, socially, mentally, and spiritually, as well as empowered families, namely families that live prosperously, progressively and independently, including families who are obedient and adhere to the rules of law, so that fulfillment of the Legal Awareness Village achievement indicators can be achieved through the strategic role of the PKK Movement in the village. This research is socio-legal research with a qualitative approach. The data used in this research are secondary (literature, documents, laws, and regulations) and primary data (interviews, questionnaires, and focused discussions) with the focus of the research carried out in ArangLimbung Village, Sei Raya District, Kubu Raya Regency. The research results show the urgency of forming a Village PKK level group which can be a forum for achieving the fulfillment of the Law Awareness Village indicators.